The Role of an Ethno-STEAM E-Module Based on Local Ecotourism and Traditional Weaving in Enhancing Students' Scientific Literacy: A Literature Review - Neli Yuliani; Sheliana Iqlima; Irman Muliadi; Lalu Azikri Amrullah; Salwa Salwa (Indonesian Journal of Teacher Education, 2026)
Scientific literacy is widely recognized as a key competency for 21st-century citizens. Nevertheless, Indonesian students’ performance in international assessments, particularly the Programme for International Student Assessment (PISA), remains relatively low. This study aims to synthesize and critically analyze empirical evidence from existing studies on the contribution of Ethno-STEAM-based science e-modules, which integrate ethnoscience, science, technology, engineering, arts, and mathematics within the context of local-weaving ecotourism in Sade Village, to students’ scientific literacy. Specifically, this review seeks to identify dominant patterns, research gaps, and both theoretical and practical implications across the selected studies. Sade Village in Central Lombok, West Nusa Tenggara, is a traditional Sasak settlement where weaving practices and local wisdom are actively maintained, providing an authentic and contextually rich resource for science learning. The study employs a Systematic Literature Review (SLR) following the PRISMA, framework, analyzing ten selected articles published between 2016 and 2024 from Google Scholar, SINTA, and ERIC. Data were analyzed thematically to identify recurring themes across the literature. The synthesis reveals that the utilization of local wisdom, integration of weaving traditions in learning, development of ethnoscience-based e-modules, and ecotourism contexts consistently contribute to improvements in scientific literacy. A notable research gap was identified: no existing study has specifically integrated the Sasak weaving ecotourism context into an empirically validated Ethno-STEAM e-module, underscoring the urgency of future developmental research in this direction.